HARNESSING ADVANCED SOFTWARE TECHNOLOGIES TO ENHANCE SCIENTIFIC LITERACY AND EXPOSURE IN THE POST-PRIMARY EDUCATION OF CROSS RIVER STATE, NIGERIA (International Journal of Functional Research in Science and Engineering (IJFRSE), 2025)
This study investigates the transformative potential of advanced software technologies in bolstering scientific literacy and exposure among post-primary students in Cross River State, Nigeria. Amid global strides in educational technology, Nigerian schools face persistent challenges, including limited access to digital tools and inadequate teacher training. Employing a descriptive survey design, data were gathered through questionnaires from 400 participants (300 students and 100 teachers) across 10 public secondary schools in Calabar. Results indicate that 70% of students lack access to computers, while 75% of teachers report insufficient training in software integration. However, 85% of respondents believe tools like virtual labs and e-learning platforms could enhance scientific understanding. Key barriers include erratic power supply (92%) and poor internet connectivity (68%). The study proposes mobile-based learning and teacher capacity-building as viable solutions. Recommendations include government-led infrastructure upgrades, curriculum reforms to embed technology, and partnerships with tech firms to provide affordable tools. This research illuminates a path toward leveraging software technologies to foster scientific literacy, equipping students for a technology-driven future.